2023
DOI: 10.1155/2023/1043369
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Evaluation of Dental Arches in Individuals with Syndromic Craniosynostosis

Abstract: Objective. Individuals with syndromic craniosynostosis present alterations in the dental arches due to anomalies caused by the early fusion of the craniomaxillary sutures. This study aimed to compare intradental and interdental dimensions between individuals with Apert and Crouzon syndromes and nonsyndromic controls. Materials and Methods. Digital models were obtained from the archive of a public tertiary care hospital. The sample consisted of 34 patients (Apert n = 18, Crouzon n = 16) and 34 nonsyndromic cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Of note, the cohort in this study ranged from infanthood to adulthood, allowing comprehensive and chronological development. Our study suggested that maxillary retrusion rapidly aggravated during the 3 to 6 years old, which corroborates with what Lu et al found, confirming that therapeutic interventions, including surgical advancement 22 or nonsurgical orthodontic maxillary expansion 23,24 should be initiated to slow pathologic deterioration. The delay of mandibular rapid aggravation indicates mandibular counterclockwise rotation might be triggered by maxillary retrusion and the covariation of maxillary and mandibular morphological variation should be further investigated to determine whether intervention should be enforced on the mandible independently or not.…”
Section: Discussionsupporting
confidence: 91%
“…Of note, the cohort in this study ranged from infanthood to adulthood, allowing comprehensive and chronological development. Our study suggested that maxillary retrusion rapidly aggravated during the 3 to 6 years old, which corroborates with what Lu et al found, confirming that therapeutic interventions, including surgical advancement 22 or nonsurgical orthodontic maxillary expansion 23,24 should be initiated to slow pathologic deterioration. The delay of mandibular rapid aggravation indicates mandibular counterclockwise rotation might be triggered by maxillary retrusion and the covariation of maxillary and mandibular morphological variation should be further investigated to determine whether intervention should be enforced on the mandible independently or not.…”
Section: Discussionsupporting
confidence: 91%
“…and CSs had an edge-to-edge bite (p < 0.001) (Pinto et al, 2023). CSs tend to have shorter and atter cranial bases, smaller orbital volumes, and cleft palates.…”
Section: Meta-analysismentioning
confidence: 92%
“…The anterior maxillary region is more affected in AS patients than in HCs but less affected in CS patients. ASs had an anterior crossbite (p < 0.001), and CSs had an edge-to-edge bite (p < 0.011)(Pinto et al, 2023).Compared with CS patients, AS patients were found to have clinical features of limb malformations. Increased mandibular asymmetry, increased lower facial height ratios, decreased transverse dimensions, an increased inclination of the palatal plane, and a more protruding mandible were observed in the AS patients.…”
mentioning
confidence: 90%
See 1 more Smart Citation